Purchase intention for organic meat among consumers in Klang Valley, Malaysia - Wong, Soo Soon (2014)
The purpose of the study was to investigate the factors that influence the consumers‘ purchase intention towards organic meat in Klang Valley based on the Theory of Planned Behaviour (TPB) and organic meat choice motives model. The data were collected by using convenience sampling in selected organic food retail shops which were located in five different towns in Klang Valley, Malaysia. A total of 400 consumers responded to the survey and data were analyzed using Statistical Package for Social Science SPSS). Descriptive and inferential statistics were used to analyze the data. Slightly more females participated in this study (51.8%) compared to males (48.2%). The mean age of the respondents was 35.4 years old. Majority of the respondents were Chinese (49.8%), followed by Malays (42.2%) and Indians (8%). The findings showed that attitude towards organic meat (r=0.602, p<0.0001), subjective norm (r=0.653, p<0.0001) and perceived behavioural control (r=0.751, p<0.0001) had strong linear positive relationship with purchase intention of organic meat. All the variables of organic meat choice motives which were food safety, meat characteristic, health consciousness and price had moderate to strong positive correlation with rvalue ranges from 0.417 to 0.681 significant at p<0.0001. Multiple regression analysis showed that perceived behavioural control, attitude towards organic meat, price and meat characteristic explained 67.6 percent of the variance in intention to purchase organic meat. The study findings indicated that purchasing of organic meat could be increased by expanding the availability of organic meat retailers, that offer good quality organic meat which are reasonably priced, and along with nurturing positive attitude of consumers towards organic meat through appropriate educational programs and campaigns.